The regulation of geoengineering technologies: the case study of cloud seeding - Protásio, Manuel (2021)
Climate Change is not a foreseeable future anymore but a glooming present to which laws must react, rather than just prevent it from happening. The current legal framework in the European Union still reflects a preventive and precautionary approach towards the environment and specifically the challenges of Climate Change. This article argues that this preventive approach, based on a strong interpretation of the precautionary principle, hinders the research and development of technologies that can be used to mitigate the current and future effects of Climate Change. Using the case study of cloud seeding, the present paper demonstrates how geoengineering technologies can be seen as cost-effective measures to prevent environmental degradation from Climate Change and how the lack of scientific certainty regarding these technologies should not be a reason to not regulate them.